Implementing Mannequin-Based Media to Assess Empathy in Vocational Students: A Case Study of Fiqh Janazah Instruction at SMK Safinatul Huda - Khoirul Anam; M. Lukman Hakim; M. David Ilham Yusuf; Ahmad Husin (ALSYS, 2026)
This study examines the use of adult and child mannequin models to evaluate and cultivate student empathy in Fiqh Janazah learning within the Love-Based Curriculum (Kurikulum Berbasis Cinta/KBC) at SMK Safinatul Huda. Using a descriptive qualitative design, data were collected over one semester through participant observation during four practical meetings, semi-structured interviews with two teachers and 12 students, and document analysis of lesson plans, assessment rubrics, and reflection journals. Teachers translated curricular competencies into affective operational objectives and developed a validated four-aspect empathy rubric covering gentleness and carefulness, protection of awrah and adab, devotion in prayer and dhikr, and teamwork and concern. The instructional process integrated pre-practice rituals, station-based simulations of bathing, shrouding, funeral prayer, and burial, observer-rated assessment, immediate feedback, and reflective journaling. The findings indicate that mannequin-based media function not only as psychomotor training tools but also as catalysts for affective learning. Students demonstrated improved gentleness, respectful handling of the models, devotional commitment, and cooperative behavior. Observation records and reflection journals further showed reduced fear and increased sincerity, with 28 of 36 students reporting emotional engagement and commitment to behavioral change. This study concludes that value-infused planning, authentic assessment, and reflective practice are essential for internalizing ihsan and empathy in Islamic vocational education. Its contribution lies in demonstrating how mannequin-based media can support affective assessment and character formation in religious practice-based learning. However, the short-term scope, rubric reliability issues, and assessor training needs indicate the importance of longitudinal evaluation, standardized affective measurement, and professional development to strengthen assessment validity and the transferability of empathic behavior.